COMPENSATOR-ADAPTIVE REACTIONS OF PATIENTS’ ORGANISM WITH GNATHIC FORM OF DENTAL OCCLUSION ANOMALIES - Dusmukhamedov, Makhmud Z. (International Journal of Psychosocial Rehabilitation, 2020)
Abstract---Background. According to the latest information about the flexibility of patients with congenital anomalies of the dentofacial system has increased.The aim of the researchwas to assess psycho-emotional state, the state of tissue hypoxia and the protective system in patients with gnathic forms of occlusion abnormalities dentition.Methods and materials. 67 patients with defects and deformations of jaws participated in this research to investigate psycho-emotional state of the patients. In order to estimate patients’ psychological condition we used clinical questionnaire and technique of emotional states self-assessment. To evaluate tissue hypoxia, hypoxemia and protective system condition in patients with gnathic forms of occlusion abnormalities, depending on the type of occlusion anomaly, patients were divided into two groups: 1stgroup included 17 patients with distal occlusion (upper macro-prognathia, lower micro-retrognathia) and 2nd group consisted of38 patients with mesial occlusion (lower macro-prognathia, upper micro-retrognathia). The control groupamounted to 8 healthy individuals without occlusion anomalies.Findings. Evaluation of HbF levels in combination with clinical data provides much more information about the development of tissue hypoxia and hypoxemia in patients with gnathic forms of occlusion abnormalities. Determination of the level of HbF in patients with denticular gnathic forms of occlusion abnormalities can be used to diagnose chronic tissue hypoxia and supports to clarify the severity of the pathological process, which allows us to predict the progression of the disease and the development of their complications.